2023
DOI: 10.1088/1361-6560/ace877
|View full text |Cite
|
Sign up to set email alerts
|

Mean dose rate in ultra-high dose rate electron irradiation is a significant predictor for O2 consumption and H2O2 yield

Abstract: Objective: The objective of this study was to investigate the impact of mean and instantaneous dose rates on the production of reactive oxygen species (ROS) during ultra-high dose rate (UHDR) radiotherapy. The study aimed to determine whether either dose rate type plays a role in driving the FLASH effect, a phenomenon where UHDR radiotherapy reduces damage to normal tissues while maintaining tumor control.
Approach: Assays of hydrogen peroxide (H2O2) production and oxygen consumption (ΔpO2) were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Among these parameters, the beam temporal structure was varied to investigate oxygen depletion in water [ 77 ], measuring O 2 content for different average and bunch dose rates of electron beams, showing a strong correlation with biological data, and supporting the role of radicals at the origin of the FLASH effect. In another study [ 78 ], the dependence of O 2 consumption and H 2 O 2 production were found to depend on the mean dose rate, with instantaneous dose rates also contributing to this effect. Concerning the type of radiation, interesting studies are finally emerging on the use of UHDR kilovoltage (kV) X-rays from a rotating-anode X-ray source for in vivo studies, making this type of radiation easily accessible at a laboratory scale compared to synchrotron radiation [ 79 ].…”
Section: Biological Mechanisms Behind the Flash Effect: The Role Of D...mentioning
confidence: 99%
“…Among these parameters, the beam temporal structure was varied to investigate oxygen depletion in water [ 77 ], measuring O 2 content for different average and bunch dose rates of electron beams, showing a strong correlation with biological data, and supporting the role of radicals at the origin of the FLASH effect. In another study [ 78 ], the dependence of O 2 consumption and H 2 O 2 production were found to depend on the mean dose rate, with instantaneous dose rates also contributing to this effect. Concerning the type of radiation, interesting studies are finally emerging on the use of UHDR kilovoltage (kV) X-rays from a rotating-anode X-ray source for in vivo studies, making this type of radiation easily accessible at a laboratory scale compared to synchrotron radiation [ 79 ].…”
Section: Biological Mechanisms Behind the Flash Effect: The Role Of D...mentioning
confidence: 99%